Konsep Pendidikan Anak Dalam Surat Luqman Ayat 12-19 Perspektif Tafsir Al-Azhar Dan Tafsir Al-MishbÄh - Eva Khofifa (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2023)
This study aims to describe the concept of children's education in QS. Luqman/31: 12-19 Tafsir Al-Azhar and Tafsir Al-Misbah and elaborate to find similarities and differences between the two interpretations. Using qualitative methods of literature study, and content analysis approach. Some of the children's education in Tafsir Al-Azhar include: fostering monotheism, moral development, attitude development, social coaching and responsibility for fostering prayer. Whereas in Al-Misbah's interpretation the concept of child education includes: the command to be grateful to Allah SWT in receiving the blessings given by Allah SWT, worship Allah SWT and not commit shirk, obligations to serve both parents, every good deed or bad deed that What is done by every human being will definitely get a reply from Allah SWT, so that he always does prayer and always does good and stays away from evil deeds, politeness in words and deeds, behaves not arrogantly in life. The similarity of the two interpretations is the use of the tahlili interpretation method and the essence of children's education including monotheism education, moral education and worship education. The difference lies in the systematic interpretation of the verse. Tafsir Al-Azhar, the presentation is written in short sections consisting of several verses with an Indonesian translation along with the Arabic text and followed by a long explanation. Tafsir Al-Misbah begins with the origin of the word, describes the meaning of the word and explains the context of the verse then seasons it with the opinions of other scholars, its relationship to other verses or the asbab an-Nuzul verse and not only explains the material taught to children but also the methodology of educating children. Meanwhile, in the interpretation of Al-Azhar, there is more exploration of subject matter for children.